2023
DOI: 10.3389/fneur.2023.1209567
|View full text |Cite
|
Sign up to set email alerts
|

Why should multiple dehiscences of the otic capsule be considered before surgically treating patients with superior semicircular canal dehiscence? A radiological monocentric review and a case series

Abstract: This review aims to draw attention to the multiple ipsilateral otic capsule dehiscences (OCDs), which may cause therapeutic failure in operated patients. A series of six severely disabled patients with symptoms and signs consistent with a superior semicircular canal dehiscence (SSCD) diagnosis, confirmed by a high-resolution CT scan, is presented here. Five of the patients underwent surgery, and in four of the cases, the postoperative results were poor and/or disappointing. The ethical principles underlying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…The lady who underwent canal plugging developed a transient global vestibular hypofunction overlapping the postoperative findings in patients after SSC occlusion in SSCD [48,50,51]. On the other hand, the man who underwent RW reinforcement developed symptoms due to a contralateral HSCD with the FN after surgery, similar to what has been described in patients with multiple third window disorders, highlighting the importance of an extensive preoperative clinical, instrumental and radiological assessment [13].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The lady who underwent canal plugging developed a transient global vestibular hypofunction overlapping the postoperative findings in patients after SSC occlusion in SSCD [48,50,51]. On the other hand, the man who underwent RW reinforcement developed symptoms due to a contralateral HSCD with the FN after surgery, similar to what has been described in patients with multiple third window disorders, highlighting the importance of an extensive preoperative clinical, instrumental and radiological assessment [13].…”
Section: Discussionsupporting
confidence: 66%
“…Even though aural fullness and autophony can also be found in both patulous Eustachian tube and SCD, patients with a patulous Eustachian tube generally have autophony for their own breath sounds, while patients with SCD usually do not [9]. Besides SCD, other conditions resulting in a TMWM have been described over the years, including an enlarged vestibular aqueduct, X-linked gusher disorder and cochlear dehiscence either involving the internal carotid artery or the facial nerve (FN) [3,5,6,[10][11][12][13][14]. Despite being rare, posterior SCD (PSCD) represents the second most common SCD after SSCD, with a 2% incidence among adult patients and a variable incidence ranging from 1.3 to 43% in the pediatric population [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is otherwise individual patient anatomic variability in SCD, and recent papers [44] showed that 18% had a concomitant additional ipsilateral dehiscence. Some of these dehiscences may have a significant impact on SVIN components.…”
Section: Characteristics Of the Nystagmus Obtained In Scd (Direction ...mentioning
confidence: 99%